Ethics in the global South - Schwartz, Michael, active 2017; Harris, Howard, active 2017 (Research in ethical issues in organizations ;, 2017)
The influence of the global South is increasing in the conduct and governance of multinationals, in the growing interest in the 'bottom of the pyramid', in the debates over the environment, trade and international law. There are questions aplenty. Complexities and tensions, differing ethical interpretations. The volume includes works by authors from the global South and contributions about ethical issues in the global South, including the responses to famine in East Africa, India and Indonesia, and the applicability of international guidelines and ethical frameworks in South Africa. Other contributions examine the roles of beliefs and philosophies in the establishment of ethical traditions.